GEODETIC SLIP RATE ESTIMATES FOR THE KUMERING AND SEMANGKO SEGMENTS OF THE SUMATERA FAULT - Irwan Meilano; Susilo Susilo; Endra Gunawan; Budi Parjanto (Jurnal Meteorologi dan Geofisika, 2021)
The Sumatran fault is a right lateral active inland fault in southern Sumatra, Indonesia. Although historical earthquake records have shown that magnitude 7 class earthquakes have occurred during the last century, the slip rates along the Sumatran fault have not been studied in detail. This is the first research using a new dense GPS array, in which stations are orthogonal to the fault, to analyze the fault slip rates along the Kumering and Semangko segments in southern Sumatra. In this study, we process GPS data from 14 campaign and continuous GPS points. The results show velocities of 14 mm/yr and 15 mm/yr for these two fault segments, respectively. Our estimated geodetic slip rate suggests that the Sumatran fault has a relatively homogeneous slip rate from southern to northern Sumatra.